2002
DOI: 10.1002/rcm.885
|View full text |Cite
|
Sign up to set email alerts
|

A top down approach to protein structural studies using chemical cross‐linking and Fourier transform mass spectrometry

Abstract: Mass spectrometric analysis of wild-type proteins that have been covalently modified by bifunctional cross-linking reagents and then digested proteolytically can be used to obtain low-resolution distance constraints, which can be useful for protein structure determination. Limitations of this approach include time-consuming separation steps, such as the separation of internally cross-linked protein monomers from covalent dimers, and a susceptibility to artifacts due to low levels of natural and man-made peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
132
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(140 citation statements)
references
References 19 publications
7
132
1
Order By: Relevance
“…We are implementing FTICR mass spectrometry, which offers distinct advantages for the analysis of complex biological samples, such as excellent mass resolution, ultra-high mass measurement accuracy, and high sensitivity [15,16] to evaluate its use in the area of cross-linking. Top-down approaches employing FTICR-MS for analyzing cross-linked products have been described by other groups [17][18][19] but, so far, that strategy has been exclusively employed to determine low-resolution three-dimensional structures of proteins from intramolecular cross-linking experiments. Our aim is to analyze the cross-linked species in a bottom-up approach, in which the cross-linked products are enzymatically or chemically digested before an FTICR-MS analysis is performed on the peptide mixtures [20,21].…”
mentioning
confidence: 99%
“…We are implementing FTICR mass spectrometry, which offers distinct advantages for the analysis of complex biological samples, such as excellent mass resolution, ultra-high mass measurement accuracy, and high sensitivity [15,16] to evaluate its use in the area of cross-linking. Top-down approaches employing FTICR-MS for analyzing cross-linked products have been described by other groups [17][18][19] but, so far, that strategy has been exclusively employed to determine low-resolution three-dimensional structures of proteins from intramolecular cross-linking experiments. Our aim is to analyze the cross-linked species in a bottom-up approach, in which the cross-linked products are enzymatically or chemically digested before an FTICR-MS analysis is performed on the peptide mixtures [20,21].…”
mentioning
confidence: 99%
“…In our own recent work, we showed that a top down approach to the localization of cross-links using FTMS could be applied to localize three cross-links in ubiquitin [7], and in a more recent publication we showed that the distance constraints can be improved by using a series of cross-linkers of different lengths [6]. However, ubiquitin has eight primary amino groups (seven on lysines and one at the amino terminus) that should be reactive with dissuccinimidyl esters, the reagents that were used in the preliminary studies described above, yet only three cross-links were observed.…”
mentioning
confidence: 99%
“…Cross-linkages may be either intramolecular or intermolecular. Intramolecular cross-linking demonstrates which regions within a protein are adjacent [1][2][3], while intermolecular cross-linking indicates adjacent regions of subunits in a protein assembly [4 -6]. To identify cross-linked residues, proteins are digested into peptides whose identities are determined by mass spectrometry (MS).…”
mentioning
confidence: 99%